Effects of oil resource endowment, natural gas and agriculture output: Policy options for inclusive growth - Ekundayo P. Mesagan; Juliet I. Adenuga (African Governance and Development Institute (AGDI), 2019)
The fact that inclusive growth involves the width of growth, benefit-sharing, and human development pertaining to health care makes this study to examine the impact of crude oil, natural gas and agriculture output on inclusive growth in Nigeria between 1970 and 2017. We use employment, life expectancy, and income per capita to capture inclusive growth, from where we compute inclusive growth index using the Principal Component Analysis. The result of the Autoregressive Distributed Lag suggests that crude oil and natural gas production insignificantly impact inclusive growth while agriculture output is significant. It means that oil resource wealth has neither been maximised to widen growth contribution nor used to deepen the growth spread in Nigeria whereas the agriculture resource is critical for inclusive growth. It is important to focus on expanding human capacity by improving employment, health care delivery, and investing in modular mechanised farming for agriculture graduates to promote inclusive growth.
Keywords: O13; Q10; Q32; Q33; 330; Crude Oil Production; Natural Gas; Agriculture Output; Inclusive Growth